Reconciliation of Cross cultural Tension in Chinua Achebe’s Marriage is a Private Affair (Patan Prospective Journal, 2022)
Cross cultural tension is one of the major themes in Chinua’s Achebe’s novels and short stories. The writer projects the same theme in his story - Marriage is a Private Affair in the context of Nigerian, African culture and tradition. This paper explores the generation gap between old and new owing to the effect of globalization, and its subsequent resolution and reconciliation. Cultural tension or conflict arises in a family or a society when new generation ruptures the old prevalent traditions. This article centers on how the Main Protagonist of the story Nnemeka, being influenced with modern culture, establishes the cultural bridge through inter-caste or inter-racial marriage, thereby challenging the old Nigerian, African tradition. Marriage is a social custom and it often occurs on the conventions of society in which people are brought up. When a person breaks the convention, it generates the conflict or tension in family and society. However, reconciliation is inevitable in the ultimate state as there is no way out. The paper conceptualizes the theoretical concept of cultural studies adopted by Stuart Hall in the light of fictional dramatization. His theory of Cultural construction refers to the elements of social and cultural characteristics as mere constructs invented by society This research attempts to answer: how does the growing globalization affect cultural taboos and rituals on Nigerian, African marital culture? The growing trend of globalization even interferes marriage custom as depicted in the Story- Marriage is a Private Affair.